Dylematy rozwoju Polski wschodniej - Mierosławska, Alicja (Dilemmas of Development of Eastern Poland, 2009)
The Operational Program Development of Eastern Poland (OPDEP) will be carried out within the years 2007-2013 in five eastern administrative regions (voivodships) of Poland exhibiting the lowest level of development. The priorities of the program are targeted towards modern economy, the support of growth centers and the development of road infrastructure. The aim of the study at hand was a thorough analysis of 117 projects included in the Program (107 of them belonged to the core group and the rest to the reserve list) categorized over the voivodships, total value and the amount of funds supply from the European Regional Development Fund (ERDF). The total value of the implemented projects amounted to 2802 million Euro, while 2002 million Euro has been supplied by the ERDF. The majority of the projects (32) will be performed in the Lubelskie voivodship. Regardless of the voivodship in question the average value of the project is small (65% does not exceed 20 million Euro) and the majority (41%) of funds is invested in road infrastructure. The largest single project which involves all analyzed regions is the development of telecommunication network worth 300 million Euro. According to the estimation the OPDEP along with other regional programs will however satisfy the investment needs of the regions only in about 30% and will thus not eliminate all existing development impairments. There is still need for an active long-term government policy on this matter. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 733-741